2004
DOI: 10.1097/01.wnf.0000136891.17006.ec
|View full text |Cite
|
Sign up to set email alerts
|

Quetiapine and Clozapine in Parkinsonian Patients With Dopaminergic Psychosis

Abstract: Quetiapine and clozapine appear equally efficacious for treatment of dopaminergic psychosis in patients with PD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
114
1
10

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(127 citation statements)
references
References 26 publications
2
114
1
10
Order By: Relevance
“…Quetiapine, another atypical antipsychotic drug, has been reported in a number of open-label studies to reduce psychosis in PD without worsening motor symptoms, but sedative and hypotensive effects also limit its tolerability (Fernandez et al, 1999Reddy et al, 2002;Mancini et al, 2004;Morgante et al, 2004;Merims et al, 2006). Furthermore, in three placebo-controlled, double-blind, randomized trials, quetiapine failed to show superiority to placebo on measures of psychosis in PDP (Ondo et al, 2005;Rabey et al, 2006;Shotbolt et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Quetiapine, another atypical antipsychotic drug, has been reported in a number of open-label studies to reduce psychosis in PD without worsening motor symptoms, but sedative and hypotensive effects also limit its tolerability (Fernandez et al, 1999Reddy et al, 2002;Mancini et al, 2004;Morgante et al, 2004;Merims et al, 2006). Furthermore, in three placebo-controlled, double-blind, randomized trials, quetiapine failed to show superiority to placebo on measures of psychosis in PDP (Ondo et al, 2005;Rabey et al, 2006;Shotbolt et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Open label trials, published after the double blind trials began reported results similar to the double blind, controlled trials [78]Results for risperidone [79][80][81][82], ziprasidone [83,84] and aripiprazole [85][86][87] have all been open label and conflicting in their outcomes, with some demonstrating worsened parkinsonism [81,83,88,89] and others reporting good tolerance [79,80,[90][91][92], without worsening of motor function. Some reports have found "non-inferiority" of drugs compared to clozapine [93][94][95]. The drugs have generally been reported helpful for the psychosis, although not uniformly.…”
Section: Managementmentioning
confidence: 99%
“…In addition, risperidone, olanzapine, ziprasidone and aripiprazole have frequently been associated with dose-dependent neuroleptic induced parkinsonism in otherwise normal psychotic patients (personal observation). Open label studies showed quetiapine to be well tolerated and an effective antipsychotic for PDP [96][97][98] and in comparison trial [95] to be non-inferior to clozapine. Unfortunately, three double blind controlled trials did not find efficacy [99][100][101], although all confirmed that the drug was free of motor worsening.…”
Section: Managementmentioning
confidence: 99%
“…Two clinical trials 46 ,47 were head-to· head comparisons of clozapine and quetiapine (Table V) Morgante et al 46 reported on a randomized, open-label, rater-blinded, comparison trial of quetiapine and dozapine, using the BPRS and CGI as the primary outcome measures; 45 patients were induded in this study, 40 of whom completed the study (completion rate, 88.9%). Three ( 13.0%) of2 3 patients in the dozapine group and 1 (4.5%) of22 patients in the quetiapine group did not complete the study.…”
Section: Comparison Studiesmentioning
confidence: 99%